Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1186/1477-7827-8-63
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 11 is upregulated in uterine lavage and endometrial cancer cells in women with endometrial carcinoma

Abstract: BackgroundInterleukin (IL) 11 is produced by human endometrium and endometrial cancer tissue. It has roles in endometrial epithelial cell adhesion and trophoblast cell invasion, two important processes in cancer progression. This study aimed to determine the levels of IL11 in uterine lavage fluid in women with endometrial cancer and postmenopausal women. It further aimed to determine the levels of IL11 protein and its signaling molecules in human endometrial cancer of varying grades, and endometrium from postm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 43 publications
(63 reference statements)
1
25
0
Order By: Relevance
“…In women with endometrial cancer, IL11 levels are elevated in uterine lavage fluid and are positively associated with higher endometrial tumor grades (16). IL11 protein (16) and mRNA (17), along with IL11Ra protein levels are progressively increased with increased endometrial tumor grade (16), which is in line with findings in other tumor types such as ovarian and colorectal (18,19).…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…In women with endometrial cancer, IL11 levels are elevated in uterine lavage fluid and are positively associated with higher endometrial tumor grades (16). IL11 protein (16) and mRNA (17), along with IL11Ra protein levels are progressively increased with increased endometrial tumor grade (16), which is in line with findings in other tumor types such as ovarian and colorectal (18,19).…”
Section: Introductionsupporting
confidence: 75%
“…We and others previously demonstrated that IL11 is upregulated in endometrial cancer in women (16,17) and we have shown that IL11 alters endometrial cancer cell migration in vitro, via STAT3 (22). This is the first study to determine a functional role for IL11 in endometrial cancer in vivo and establish that IL11 inhibition impairs endometrial tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The genes spans 7 kb and consists of 5 exons and 4 introns (13). Numerous studies have suggested that IL-11 has roles in human gastric, prostate and bone cancer, and endometrial carcinoma (14). The uterine washing level of IL-11 has been found to be elevated and to play a complex role in the progression of endometrial carcinoma.…”
Section: Introductionmentioning
confidence: 99%